2019
DOI: 10.1177/0954406219886325
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration response of carbon nanotube reinforced pretwisted conical shell under thermal environment

Abstract: Finite element procedure is employed to analyze the free vibration characteristics of rotating functionally graded carbon nanotubes reinforced composite conical shell with pretwist under the thermal environment. In this paper, four types of carbon nanotube grading are considered, wherein the distribution of carbon nanotubes are made through the thickness direction of the conical shell. An eight-noded isoparametric shell element is used in the present formulation to model the panel based on the first-order shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…The above equation (37) is solved iteratively to find the natural frequency of the system. 3235 It is observed that after three iterations the result converges. The natural frequencies (ωn) are computed by using standard Eigen value solver algorithm.…”
Section: Hybrid Cnt Nanocompositementioning
confidence: 91%
See 2 more Smart Citations
“…The above equation (37) is solved iteratively to find the natural frequency of the system. 3235 It is observed that after three iterations the result converges. The natural frequencies (ωn) are computed by using standard Eigen value solver algorithm.…”
Section: Hybrid Cnt Nanocompositementioning
confidence: 91%
“…The formulation for obtaining the varying radius of curvature (Ry) of the conical shell in the co-ordinate system is explained in Maji et al 35 The present investigation is carried out on both the pretwisted and untwisted conical shell geometry. The z-coordinate of the conical shallow shell can be defined as…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this investigation, first-order shear deformation theory was used and the effects of temperature as well as the arrangement of the various carbon nanotube on the natural frequencies were investigated. Maji et al 14 studied free vibration analysis of a carbon nanotube conical shell subjected to temperature changes. In this investigation, a numerical study based on the finite element method was introduced to calculate the natural frequency of the shell.…”
Section: Introductionmentioning
confidence: 99%
“…Maji et al. 37 studied the free vibration behavior of pre-twisted conical shells made of nanocomposite subjected to thermal load using the finite element method. Nguyen et al.…”
Section: Introductionmentioning
confidence: 99%